2018
DOI: 10.1007/s11365-018-0499-2
|View full text |Cite
|
Sign up to set email alerts
|

Benefiting from economic crisis? Strategic orientation effects, trade-offs, and configurations with resource availability on SME performance

Abstract: While there is growing interest in exploring strategic orientations, their interaction, and impact on firm performance, most research has been conducted within stable economic environments. Taking into consideration economic instability, it is timely to develop a more nuanced understanding of how economic crises may affect key strategic orientation prescriptions. In this research, we examine entrepreneurial and market orientations as means through which firms may operate within an economic crisis to seize avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 101 publications
(166 reference statements)
4
110
0
6
Order By: Relevance
“…In such periods, entrepreneurs face serious threats that affect their financial situation and, ultimately, their very survival [Kunc, Bhandari, 2011;Pal et al, 2014]. However, deep economic shocks also create new opportunities [Beliaeva et al, 2018;Laskovaia et al, 2019;Pearce, Michael, 2006] oped and emerging markets indicate that increased economic pressure often helps a firm make creative decisions that positively affect companies' financial performance [Beliaeva et al, 2018;Hausman, Johnston, 2014]. Players who rely on innovation also strengthen their market positions and leadership [Drickhamer, 2003;Guellec, Wunsch-Vincent, 2009;Pearce, Michael, 2006].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such periods, entrepreneurs face serious threats that affect their financial situation and, ultimately, their very survival [Kunc, Bhandari, 2011;Pal et al, 2014]. However, deep economic shocks also create new opportunities [Beliaeva et al, 2018;Laskovaia et al, 2019;Pearce, Michael, 2006] oped and emerging markets indicate that increased economic pressure often helps a firm make creative decisions that positively affect companies' financial performance [Beliaeva et al, 2018;Hausman, Johnston, 2014]. Players who rely on innovation also strengthen their market positions and leadership [Drickhamer, 2003;Guellec, Wunsch-Vincent, 2009;Pearce, Michael, 2006].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Plus, SMEs are more dependent on external resources [Baum, Oliver, 1996] and become hostages to the modest scale of their operations [Audretsch, Mahmood, 1994]. However, crises also open potential opportunities for SMEs [Beliaeva et al, 2018;Soininen et al, 2012].…”
Section: The Entrepreneurial Component Of Se and Smes' Performance Dumentioning
confidence: 99%
See 1 more Smart Citation
“…Top managers' attention to the external environment, in general, increases the degree of internationalization (Levy, 2005). Information on markets, customers, and competitors provides important clues to new business opportunities (Beliaeva, Shirokova, Wales, & Gafforova, 2020; Martin, Javalgi, & Ciravegna, 2020; Zahra, 2005). Understanding the external environment can lead to higher value creation when firms possess adequate internal capabilities (Lee, Lee, & Pennings, 2001).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Previous studies have identified various types of SO dimensions including market orientation (MO), customer orientation (CO), and entrepreneurial orientation (EO) all of which play a vital role for firms in acquiring superior performance (Beliaeva et al, 2018;Engelen et al, 2015;Jaworski and Kohli, 1993;Morgan et al, 2009;Sisay et al, 2017;Zhang and Yang, 2018). SO, in such context, refers to the processes, principles, practices, and decision-making techniques that direct organisational activities (Herath and Mahmood, 2014;Zhou and Li, 2010).…”
mentioning
confidence: 99%